Uá¹¡irul TasyÄ«âu fi Taá¹£Ä«á¸¥ul HadÄ«á¹¡i: DurÄsatu âAn Taá¹£Ä«á¸¥i AbÄ« âAbdillÄá¸¥il HÄkimil NisÄbawÄ« HadÄ«á¹¡iyyul á¹ªÄ«ru wa min Kuntu MaulÄhu fiâliyyu MaulÄhu fÄ« KitÄbil Mustadriku âAla á¹¢aá¸¥Ä«á¸¥Ä«na - Gazali, Abdul Malik (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2013)
-